A quasi-dynamic model and thermal analysis for vapor chambers with multiple heat sources based on thermal resistance network model. (July 2022) - Dan, Dan; Li, Weifeng; Zhang, Yangjun; Xie, Yi
Abstract: The heat and mass transfer mechanism in a vapor chamber is a complex process. The thermal resistance network model is an effective tool to describe the heat transfer behavior of a vapor chamber (VC). An improved quasi-dynamic multi heat source model has been developed in this study to analyze the temperature distribution of a vapor chamber with multiple heat sources under dynamic operating conditions. The accuracy of the proposed model has been validated by experiments. The influence of the VC thickness and thickness ratio has also been analyzed. Different heat source inputs have been used to study the startup characteristics of the vapor chamber. The results from simulations reveal that the optimum thickness ratio for a VC depends on the thermal resistance as well as heat transfer limit. Under the same cooling conditions, a longer startup time for a VC was observed with the increase in heating power. In addition to this, the thermal resistance of a vapor chamber was found to increase slightly at a higher temperature. The model in this study has certain guiding significance for the analysis of heat transfer and the design of a VC under various working conditions. Highlights: Thermal resistance network model for vapor chambers with multiple heat sources is established. Quasi-dynamic approach for transient analysis with high accuracy. The influences of thickness and optimum thickness ratio are analyzed. Startup characteristics and thermal resistance are analyzed.